Evidence for a chondritic impactor, evaporation-condensation effects and melting of the Precambrian basement beneath the 'target' Deccan basalts at Lonar crater, India. (15th October 2017) - Das Gupta, Rahul; Banerjee, Anupam; Goderis, Steven; Claeys, Philippe; Vanhaecke, Frank; Chakrabarti, Ramananda
Abstract: The ∼1.88 km diameter Lonar impact crater formed ∼570 ka ago and is an almost circular depression hosted entirely in the Poladpur suite of the ∼65 Ma old basalts of the Deccan Traps. To understand the effects of impact cratering on basaltic targets, commonly found on the surfaces of inner Solar System planetary bodies, major and trace element concentrations as well as Nd and Sr isotopic compositions were determined on a suite of selected samples composed of: basalts, a red bole sample, which is a product of basalt alteration, impact breccia, and impact glasses, either in the form of spherules (<1 mm in diameter) or non-spherical impact glasses (>1 mm and <1 cm). These data include the first highly siderophile element (HSE) concentrations for the Lonar spherules. The chemical index of alteration (CIA) values for the basalts and impact breccia (36.4–42.7) are low while the red bole sample shows a high CIA value (55.6 in the acid-leached sample), consistent with its origin by aqueous alteration of the basalts. The Lonar spherules are classified into two main groups based on their CIA values. Most spherules show low CIA values (Group 1: 34.7–40.5) overlapping with the basalts and impact breccia, while seven spherules show significantly higher CIA values (Group 2: >43.0). The Group 1 spherules are further subdivided into Groups 1a and 1b, with Group 1a spherules showing higher Ni and mostly higher Cr compared to the Group 1b spherules. Iridium and Cr concentrations of the spherules are consistent with the admixture of 1–8 wt% of a chondritic impactor to the basaltic target rocks. The impactor contribution is most prominent in the Group 1a and Group 2 spherules, which show higher Ni/Co, Ni/Cr and Cr/Co ratios compared to the target basalts. In contrast, the Group 1b spherules show major and trace element compositions that overlap with those of the impact breccia and are characterized by high EFTh (Enrichment Factor for Th defined as the Nb-normalized concentration of Th relative to that of the average basalt) as well as fractionated La/Sm(N), and higher large ion lithophile element (LILE) concentrations compared to the basalts. The relatively more radiogenic Sr and less radiogenic Nd isotopic composition of the impact breccia and non-spherical impact glasses compared to the target basalts are consistent with melting and mixing of the Precambrian basement beneath the Deccan basalt with up to 15 wt% contribution of the basement to these samples. Variations in the moderately siderophile element (MSE) concentration ratios of the impact breccia as well as all the spherules are best explained by contributions from three components – a chondritic impactor, the basaltic target rocks at Lonar and the basement underlying the Deccan basalts. The large variations in concentrations of volatile elements like Zn and Cu and correlated variations of EFCu -EFZn, EFPb -EFZn, EFK -EFZn and EFNa -EFZn, particularly in the Group 1a spherules, are best explained by evaporation-condensation effects during impact. While most spherules, irrespective of their general major and trace element composition, show a loss in volatile elements (e.g., Zn and Cu) relative to the target basalts, some spherules, mainly of Group 1, display enrichments in these elements that are interpreted to reflect the unique preservation of volatile-rich vapour condensates resulting from geochemical fractionation in a vertical direction within the vapour cloud.